2005
DOI: 10.1071/ar04300
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of phalaris (Phalaris aquatica L.) germplasm for persistence under grazing on the North-West Slopes, New South Wales

Abstract: The survival of available cultivars of introduced temperate perennial grasses has been less than adequate under grazing on the North-West Slopes of New South Wales. A wide range of germplasm of the Mediterranean perennial grass, phalaris (Phalaris aquatica L.), was assessed for persistence, seedling vigour, winter yield potential, time of reproductive development, and summer dormancy in grazed swards at 3 sites (Manilla, Tamworth, Purlewaugh) from 1998 to 2001. The aim was to understand population characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 25 publications
2
33
1
Order By: Relevance
“…However, the previous studies indicated that early-flowering ecotypes of orchardgrass (Dactylis glomerata L.) had more ability to survive severe drought (Volaire et al, 1998;Shaimi et al, 2009). In tall fescue (Norton et al, 2006b) and Harding grass (Phalaris aquatica L.) (Culvenor and Boschma, 2005), incomplete dormancy has been correlated with superior survival and autumn regrowth after severe summer drought when comparing incompletely dormant cultivars and nondormant controls. These observations demonstrated that the more summer dormant genotypes were the later-emerging ones and had more chlorophyll content, RWC, and WSC in their leaves.…”
Section: Resultsmentioning
confidence: 94%
“…However, the previous studies indicated that early-flowering ecotypes of orchardgrass (Dactylis glomerata L.) had more ability to survive severe drought (Volaire et al, 1998;Shaimi et al, 2009). In tall fescue (Norton et al, 2006b) and Harding grass (Phalaris aquatica L.) (Culvenor and Boschma, 2005), incomplete dormancy has been correlated with superior survival and autumn regrowth after severe summer drought when comparing incompletely dormant cultivars and nondormant controls. These observations demonstrated that the more summer dormant genotypes were the later-emerging ones and had more chlorophyll content, RWC, and WSC in their leaves.…”
Section: Resultsmentioning
confidence: 94%
“…Thus, in those regions with mild winters, including south-west Western Australia and the northern inland New South Wales region of south-eastern Australia, significant development of pasture technology based on C4 warm-season grasses is occurring. While some of this development is based on the perception that such species will be better adapted to future climates (Timbal et al 2006;Charles and Fu 2012), some is based on observations that there are few well-adapted, persistent C3 cool-season grasses available to commercial agriculture particularly in northern NSW where summer rainfall predominates (Culvenor and Boschma 2005). Indeed, early indications in northern inland NSW suggest that C4 grass species have better adaptation (Harris et al 2009) although in the cooler, frost-prone Tableland districts of this region C3 grasses are likely to remain dominant.…”
Section: The Role Of C3 Versus C4 Perennial Forage Grassesmentioning
confidence: 99%
“…Summer dormancy is a trait which has evolved primarily for enhancing plant survival and is expressed by some of the cool-season perennial grasses mainly originating in semi-arid and arid Mediterranean climates where the summer-dry period typically lasts 4 months or more (Cooper 1963). Recent research has demonstrated this trait to be very powerful in improving survival over long and intense dry spells in the field with a suite of papers demonstrating the utility of the trait in cocksfoot and tall fescue in the Mediterranean Basin (Volaire 2002;Volaire et al 2005;Norton et al 2006a;Norton et al 2006b;Shaimi et al 2009;Pecetti et al 2009;Annicchiarico et al 2011), southern USA (Malinowski et al 2005;Malinowski et al 2009) and southeastern Australia (Culvenor and Boschma 2005;Norton et al 2001;Hackney et al 2006;Hayes et al 2010a).…”
Section: Summer Dormancy To Improve Survival Of Extended Extreme Dromentioning
confidence: 99%
“…That collection awaits thorough examination in Australia although some workers have looked at some of the grass accessions (Jahufer and Reed 2001;Culvenor and Boschma 2005;Harris et al 2008). The poor persistence of summer-active grasses, viz.…”
Section: Winter Growthmentioning
confidence: 99%